Reliability and validity of a mobile home pelvic floor muscle trainer: The Elvie Trainer. Issue 6 (18th June 2020) - Czyrnyj, Catriona S.; Bérubé, Marie‐Ève; Brooks, Kaylee; Varette, Kevin; McLean, Linda
Abstract: Aims: Reliability and validity of force measurement and task detection by the Elvie Trainer were evaluated against an intravaginal dynamometer (IVD) and ultrasound (US) imaging. Methods: Women were recruited from local physiotherapy clinics. At the first visit, pelvic floor muscle (PFM) strength and tone were assessed manually. Women performed two sets of three repetitions of rest, PFM maximal voluntary contraction (MVC), and maximal Valsalva maneuver (MVM) tasks in supine and standing, with the Elvie Trainer in situ. Women performed another set of rest and MVC repetitions with a custom IVD in situ. At the second visit, PFM strength and tone were reassessed manually. Women performed two sets of three repetitions of the rest, PFM MVC, and MVM tasks in supine and standing, with the Elvie Trainer in situ. Concurrent US imaging was then acquired during a final set of PFM MVC and MVM repetitions in supine and standing, while the Elvie Trainer remained in situ. Reliability was evaluated using intraclass correlation coefficients. Validity was evaluated using Spearman's/Pearson's correlations and receiver operator characteristic curves. Results: Thirty women participated in the study. The Elvie Trainer MVC force outcomes exhibited excellent within‐day and good between‐day reliability, but were significantly lower than IVD measures, and exhibited poor relationships with IVD force outcomes. The Elvie Trainer was able to specify correct/incorrect performance of a PFM MVC. Conclusions: The Elvie Trainer exhibits acceptable within‐day and between‐day reliability and can detect the correct performance of PFM MVCs; however, force measurements are not valid indicators of PFM strength and should not be used to measure outcomes.